Plant-produced chimeric virus-like particles - a new generation vaccine against African horse sickness - Daria A. Rutkowska; Nobalanda B. Mokoena; Tsepo L. Tsekoa; Vusi S. Dibakwane; Martha M. O’Kennedy (BMC Veterinary Research, 2019)
Abstract Background African horse sickness (AHS) is a severe arthropod-borne viral disease of equids, with a mortality rate of up to 95% in susceptible naïve horses. Due to safety concerns with the current live, attenuated AHS vaccine, alternate safe and effective vaccination strategies such as virus-like particles (VLPs) are being investigated. Transient plant-based expression systems are a rapid and highly scalable means of producing such African horse sickness virus (AHSV) VLPs for vaccine purposes. Results In this study, we demonstrated that transient co-expression of the four AHSV capsid proteins in agroinfiltrated Nicotiana benthamiana dXT/FT plants not only allowed for the assembly of homogenous AHSV-1 VLPs but also single, double and triple chimeric VLPs, where one capsid protein originated from one AHS serotype and at least one other capsid protein originated from another AHS serotype. Following optimisation of a large scale VLP purification procedure, the safety and immunogenicity of the plant-produced, triple chimeric AHSV-6 VLPs was confirmed in horses, the target species. Conclusions We have successfully shown assembly of single and double chimeric AHSV-7 VLPs, as well as triple chimeric AHSV-6 VLPs, in Nicotiana benthamiana dXT/FT plants. Plant produced chimeric AHSV-6 VLPs were found to be safe for administration into 6 month old foals as well as capable of eliciting a weak neutralizing humoral immune response in these target animals against homologous AHSV virus.